2011
DOI: 10.1103/physrevlett.106.118102
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Stability of Polypeptide Helices: Critical Role of van der Waals Interactions

Abstract: Folding and unfolding processes are important for the functional capability of polypeptides and proteins. In contrast with a physiological environment (solvated or condensed phases), an in vacuo study provides well-defined ''clean room'' conditions to analyze the intramolecular interactions that largely control the structure, stability, and folding or unfolding dynamics. Here we show that a proper consideration of van der Waals (vdW) dispersion forces in density-functional theory (DFT) is essential, and a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(134 citation statements)
references
References 36 publications
(74 reference statements)
14
120
0
Order By: Relevance
“…102,335−338 In a recent AIMD study, 334 it was shown that the inclusion of vdW forces can explain the notable stability of polyalanine (Ac-Ala n -LysH + ) helices up to a temperature of 725 K. 339 Figure 12 illustrates the fact that AIMD simulations at the PBE and PBE+TS levels of theory paint very different pictures of the dynamical helix structure over a wide range of temperatures. For instance, AIMD simulations at 700 K with PBE+TS give a structure that is comprised of both α and 3 10 -helical motifs with an overall helical structure that is preserved after 65 ps of simulation, whereas PBE predicts that the α-helical motifs quickly disappear within 5−7 ps, in contradiction to the experimental evidence.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…102,335−338 In a recent AIMD study, 334 it was shown that the inclusion of vdW forces can explain the notable stability of polyalanine (Ac-Ala n -LysH + ) helices up to a temperature of 725 K. 339 Figure 12 illustrates the fact that AIMD simulations at the PBE and PBE+TS levels of theory paint very different pictures of the dynamical helix structure over a wide range of temperatures. For instance, AIMD simulations at 700 K with PBE+TS give a structure that is comprised of both α and 3 10 -helical motifs with an overall helical structure that is preserved after 65 ps of simulation, whereas PBE predicts that the α-helical motifs quickly disappear within 5−7 ps, in contradiction to the experimental evidence.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…59 Moreover, advances in computer technology have allowed researchers to perform calculations with progressively larger basis sets and higher levels of theory. 1012 Earlier work 10,11,1315 shows that the inclusion of electron correlation in QM calculations affects to different degrees the conformational propensity of small peptides and the stability of helical motifs. Accounting for electron correlation in an approximate fashion, less computationally expensive methods based on density functional theory (DFT) have often provided a speedy and reliable description of the conformational energy of minimal peptide models.…”
Section: Introductionmentioning
confidence: 99%
“…The primary challenge associated with investigating these issues is to model accurately the broad range of molecular forces involved in ion complexation, in particular, polarization and dispersion, which contribute nontrivially to ion-ligand and ligandligand energetics (23)(24)(25). A consistent first-principles approach is therefore essential.…”
mentioning
confidence: 99%